2019
DOI: 10.1108/ijopm-02-2019-0150
|View full text |Cite
|
Sign up to set email alerts
|

The role of organizational climate in setting project goals

Abstract: Purpose Project goal setting, led by a project proposal development team, is an important operations process because effective goal setting aligned with the operations strategy can enhance project investment decision making, project success and thereby operations performance. The purpose of this paper is to argue that because of the strategic nature of this task, the organizational climate (OC) that the proposal development team works in is critical for the effectiveness of their goal setting. Design/methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Past studies demonstrated the need for top management support as a critical factor in the different project stages [ 25 ]. However, researchers scarcely discussed the reciprocal role of leadership and top management support in goal clarity [ 26 ]. Top management support is answerable for plan construction, and it must include relevant information and experience on the prevalent scenarios within organisations during the project periods.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies demonstrated the need for top management support as a critical factor in the different project stages [ 25 ]. However, researchers scarcely discussed the reciprocal role of leadership and top management support in goal clarity [ 26 ]. Top management support is answerable for plan construction, and it must include relevant information and experience on the prevalent scenarios within organisations during the project periods.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the challenges these TC create can assist project managers in enhancing communication and engagement with their stakeholders. With enhanced communication, project managers can identify opportunities to align the goals of commissioned stakeholders with the target benefits of the project, as an effective project management process is one where commissioned stakeholders understand the shared project goals (Zwikael and Meredith, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Organizational climate can be defined as the replicating patterns of attitudes, feelings and behaviors of employees towards and within their workplace environment (Zwikael and Meredith, 2019;Punwatkar and Verghese, 2018). It has a widespread effect on an organization as a whole, from leadership behavior, through policies and practices, to safety, creativity, innovation and incentives (Zwikael and Meredith, 2019;Hannevik et al, 2014). The concept of organizational climate has been outlined as multidimensional (Coda et al, 2015).…”
Section: Organizational Climatementioning
confidence: 99%